Xanthogranulomatous osteomyelitis of ulna mimicking neoplasm - Mathew Manoj; Saikia Uma N; Vankalakunti Mahesha; Kang Mandeep (World Journal of Surgical Oncology, 2007)
Abstract Background Xanthogranulomatous osteomyelitis often presents as a severe chronic inflammation associated with pain, fever, and leukocytosis. It may mimic carcinoma in the involved organs. Case presentation A 50-year-old post-menopausal woman presented with a 2 year history of increasing swelling in the extensor aspect of her right forearm. Plain X-ray revealed an ill-defined expansile osteolytic lesion in the diaphysis of ulna. The gross, microscopic and ultrastructure findings of the curettage specimen was consistent with xanthogranulomatous osteomyelitis. Conclusion This case highlights the rare occurrence of xanthogranulomatous osteomyelitis involving ulna, which can mimic as a primary or secondary bone tumors. A correct diagnosis can only be made on histopathological examination.